Dominican Republic : Technical Assistance Report-Report of the Technical Assistance Mission on Financial Accounts Topics (March 16-26, 2015). (IMF Staff Country Reports; Country Report ;, 2018)
As part of the Regional Harmonization Project on External Sector Statistics (RHPESS) of the Central America, Panama, Dominican Republic Regional Technical Assistance Center (CAPTAC-DR) member countries, a technical assistance (TA) mission on Financial Account Topics visited the Central Bank of the Dominican Republic (BCRD) on March 16-26, 2015. The objective of the TA mission was to assist the BCRD in further improving the external sector statistics (ESS). The BCRD is responsible for compiling the balance of payments (BP), international investment position (IIP), and external debt statistics (EDS). The mission focused on following up on the recommendations provided to the BCRD on the Coordinated Direct Investment Survey (CDIS) and the Coordinated Portfolio Investment Survey (CPIS) during previous a TAmission. The mission work included review/revision of (i) direct investment questionnaires; (ii) memorandum data received from the Banking Superintendence on banking portfolio assets; and (iii) debt information from business surveys.